The effect of chaperonin buffering on protein evolution. - FARES, MARIO (My University, 2010)
Molecular chaperones are highly conserved and ubiquitous proteins that help other proteins in the cell to fold. Pioneering work by Rutherford and Lindquist suggested that the chaperone Hsp90 could buffer (that is, suppress) phenotypic variation in its client proteins, and that alternate periods of buffering and expression of these variants might be important in adaptive evolution. More recently, Tokuriki and Tawfik presented an explicit mechanism for chaperone-dependent evolution, in which the E. coli chaperonin GroEL facilitated the folding of clients that had accumulated structurally-destabilizing but neofunctionalizing mutations in the protein core. But how important an evolutionary force is chaperonin-mediated buffering in nature? Here, we address this question by modeling the per-residue evolutionary rate of the crystallized E. coli proteome, evaluating the relative contributions of chaperonin buffering, functional importance, and structural features such as residue contact density. Previous findings suggest an interaction between codon bias and GroEL in limiting the effects of misfolding errors. Our results suggest that the buffering of deleterious mutations by GroEL increases the evolutionary rate of client proteins. We then examine the evolutionary fate of GroEL clients in the Mycoplasmas, a group of bacteria containing the only known organisms that lack chaperonins. We show that GroEL was lost once in the common ancestor of a monophyletic subgroup of Mycoplasmas, and we evaluate the effect of this loss on the subsequent evolution of client proteins, providing evidence that client homologs in 11 Mycoplasma species have lost their obligate dependency on GroEL for folding. Our analyses indicate that individual molecules such as chaperonins can have significant effects on proteome evolution through their modulation of protein folding.
PUBLISHED
Keywords: Genetics; Molecular chaperones; Genes & Society